Sayyid Amir Ali dan Pemikirannya - Nisa, Salikun (STUDIA: JURNAL HASIL PENELITIAN MAHASISWA, 2019)
Sayyid Amir Ali is an Islamic renewal figure from India, he is successor of his teacher, Sayyid Ahmad Khan. Sayyid Amir Ali is a figure of renewal of Islamic thought that is famous for it’s rational, but rational is always true. Sayyid Amir Ali is a figure of renewal of Islamic thought who understands qodariyah, because he wants to restore the glory of Islam that has advanced and also because he is a student of Sayyid Ahmad Khan. Sayyid Amir Ali has many works in the form of books, such as The Spirit Of Islam, one of his most famous books. Then, because his rational thinking also has others works, namely Islam is the only most true and rational religion, both Islam places woman in an honorable position, and the third is Islam the only religion that removes the system slavery and finally the existence of life after the life of the world, that is, the hereafter.